The Effect of Mol of Rice Water Waste and Kepok Banana Peel to The Growth of Brassica rapa chinensis - Yuliana, Meta; Dewi, Belia Murni; Teristiandi, Novin (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2023)
MOL is fermented solution by microbes from organic ingredients such as banana peel. MOL are useful in accelerating the destruction of organic materials and can be used as organic containing NPK fertilizer . This study aims to know the effect of the mixed of rice washing water and banana peel as MOL solution to the growth of pakcoy plants (Brassica rapa chinensis) and the its best concentration. The research design used in this study was a completely randomized design (RAL) consisting of 5 treatments and 5 replications. The treatments in this study were P0 (control) P1 (10%) P2 (20%) P3 (30%) and P4 (40%). The data were analyzed using analysis of variance (ANOVA) and continued with the Duncan/DMRT test (Duncan Multipe Range Test) at a significance level of 5%. The results showed that the MOL of kepok banana peel affects the growth of pakcoy plants on certain parameters, namely wet weight, dry weight and plant root length but not for the height and number of leaves. P2 treatment(20%) showed the best results.